The University of Cambridge in the age of Atlantic slavery - Bell-Romero, Nicolas (Cambridge University Press, 2026)
In this powerful history of the University of Cambridge, Nicolas Bell-Romero considers the nature and extent of Britain's connections to enslavement. His research moves beyond traditional approaches which focus on direct and indirect economic ties to enslavement or on the slave trading hubs of Liverpool and Bristol. From the beginnings of North American colonisation to the end of the American Civil War, the story of Cambridge reveals the vast spectrum of interconnections that university students, alumni, fellows, professors, and benefactors had to Britain's Atlantic slave empire - in dining halls, debating chambers, scientific societies or lobby groups. Following the stories of these middling and elite men as they became influential agents around the empire, Bell-Romero uncovers the extent to which the problem of slavery was an inextricable feature of social, economic, cultural, and intellectual life. This title is also available as open access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 15 Sep 2025).
Keywords: University of Cambridge -- History; Slave trade -- Great Britain -- History; Enslaved persons -- Great Britain -- History.; Universities and colleges -- Great Britain -- Colonies -- History.; Antislavery movements -- Great Britain -- History.